2012
DOI: 10.1016/j.ygcen.2011.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and food restriction on the reproductive physiology of female California mice

Abstract: Many temperate-zone animals use changes in photoperiod to time breeding. Shorter term cues, like food availability, are integrated with photoperiod to adjust reproductive timing under unexpected conditions. Many mice of the genus Peromyscus breed in the summer. California mice (Peromyscus californicus), however, can breed year round, but tend to begin breeding in the winter. Glial cells may be involved in transduction of environmental signals that regulate gonadotrophin releasing hormone (GnRH) activity. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Mice were maintained on a 16 h light/8 h dark cycle (lights off 1400 PST). Unlike other species of Peromyscus , the California mouse reproductive system is not suppressed under winter-like short day light cycles (Steinman et al, 2012). All mice were 3 month old adults and housed in cages of 2-3 same sex individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were maintained on a 16 h light/8 h dark cycle (lights off 1400 PST). Unlike other species of Peromyscus , the California mouse reproductive system is not suppressed under winter-like short day light cycles (Steinman et al, 2012). All mice were 3 month old adults and housed in cages of 2-3 same sex individuals.…”
Section: Methodsmentioning
confidence: 99%
“…In white-footed mice (Peromyscus leucopus) and Siberian hamster (Phodopus sungorus) kept under LD conditions, 70% food restriction from ad libitum feeding resulted in a significant decrease in reproductive organ masses (Young et al, 2000;Zysling et al, 2009). Consistently, the inhibitory effect of food restriction on reproductive activity was also demonstrated in other rodent species under both LD and SD conditions (Edmonds et al, 2003;Nelson et al, 1992;Steinman et al, 2012), including the closely related A. cahirinus (Bukovetzky et al, 2012). Reproductive hiatus during unfavorable environmental conditions such as food restriction and water deprivation is expected to play an important role in survival, where energy is allocated to cover maintenance of important homeostatic processes for survival (Hart and Turturro, 1998;Kirkwood, 1992;Shanley and Kirkwood, 2000).…”
Section: Discussionmentioning
confidence: 60%
“…Reproduction is energetically costly and limiting it during challenging energetic conditions such as food shortage is a life history trait (Speakman, 2008). Results of several studies revealed that food restriction can limit several reproductive processes, including gonadotropin and gonadal hormone secretions, spermatogenesis and reproductive organ development (Blank and Desjardins, 1985;Edmonds et al, 2003;Nelson et al, 1992;Steinman et al, 2012;Young et al, 2000;Zysling et al, 2009). The energy-induced reproductive cessation is expected to be mediated by complex interactions between several hormones that regulate metabolism and development throughout the body and modulate reproduction, by interacting with the hypothalamic-pituitary-gonadal axis (Martin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the precise significance of this correlation warrants further study, but perhaps it reflects individual differences in glial differentiation(Kalman et al, 1998). It is notable that in California mice ( Peromyscus californicus) the number of putative tanycytic fibers contacting the edge of the ME-EZ seems to be negatively associated with relative uterine weight (Steinman et al, 2012), so there is evidence for this glial parameter to serve as a measure of reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…The number of finger-like vimentin-immunoreactive glial terminals that were abutting the edge of the ME-EZ where the basal lamina of the portal vasculature is found was performed using a previously described method (Steinman et al, 2012). Images were photographed on a 63X objective and the fibers contacting the edge of the ME-EZ were manually counted from within a box occupying 0.013 mm 2 along the left medioventral edge (right, if left was damaged) of the ME-EZ.…”
Section: Methodsmentioning
confidence: 99%